Francesco Massa and Maureen Attali (Eds.). Shared Religious Sites in Late Antiquity: Negotiating Cultural and Ritual Identities in the Eastern Roman Empire - Urbano, Arthur P. (Studies in Christian-Jewish Relations, 2024)
No abstract is available.